Advanced Glycation End Products: Do They Impair Bone Health in Diabetes? - Papachristou, Stella; Rizzo, Manfredi; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2022)
In diabetes mellitus (DM), there is increased formation and accumulation of advanced glycation end products (AGEs), which represent a heterogeneous class of molecules produced by non-enzymatic glycation of various molecules during long-term hyperglycaemia. Several studies have examined the role of AGEs in DM complications. Accumulating evidence suggests that AGEs affect bone metabolism. New knowledge indicates that they may play a role in bone disease among DM subjects. More data are now needed to clarify their role and to explore new AGEs-based therapeutic options for optimal bone health in DM.
Keywords: advanced glycation end products; bone formation; complications; diabetes mellitus